A.I.I.S.H. norms on some aspects of child development - Hegde MN (Journal of All India Institute of Speech and Hearing, 1971)
The diagnosis of normal development of a child is of both practical and theoretical importance. A clinician who is engaged in evaluating the development of a child exhibiting one or more of several clinical conditions like mental deficiency, speech and hearing impairment, neurotic behaviour and so on faces the practical need for having data on normal development. Such data will help the clinician in diagnosing the condition and also in predicting future behaviour.